2021
DOI: 10.1021/acs.jpclett.1c00181
|View full text |Cite
|
Sign up to set email alerts
|

Mobility of Cu Ions in Cu-SSZ-13 Determines the Reactivity of Selective Catalytic Reduction of NOx with NH3

Abstract: Selective catalytic reduction of NO x with NH 3 (NH 3 − SCR) in Cu-SSZ-13 has been proposed to have a unique homogeneouslike mechanism governed by the spatial proximity of mobile Cu ions. Among factors that determine the proximity, the effect of ion density on the SCR reaction is well established; however, it has not been verified how the different mobility of the Cu ion influences the SCR reaction. Herein, we try to reveal the mobility-dependent SCR reaction by controlling the Cu species with different ion mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
35
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 43 publications
(35 citation statements)
references
References 43 publications
0
35
0
Order By: Relevance
“…V- and Cu-based catalysts have been thoroughly investigated for NH 3 -SCR at the molecular level over the past four decades. Although the mechanism of NH 3 -SCR with these catalysts has been separately discussed, a detailed literature survey suggests mechanistic similarities between V and Cu catalysts, as well as common unresolved issues regarding the NH 3 -SCR mechanism. The common features of the NH 3 -SCR mechanisms featuring V and Cu catalysts are depicted in Figure A,B.…”
Section: Introductionmentioning
confidence: 99%
“…V- and Cu-based catalysts have been thoroughly investigated for NH 3 -SCR at the molecular level over the past four decades. Although the mechanism of NH 3 -SCR with these catalysts has been separately discussed, a detailed literature survey suggests mechanistic similarities between V and Cu catalysts, as well as common unresolved issues regarding the NH 3 -SCR mechanism. The common features of the NH 3 -SCR mechanisms featuring V and Cu catalysts are depicted in Figure A,B.…”
Section: Introductionmentioning
confidence: 99%
“…51,161,175 The mobility of the Cu ions ( i.e. , one [Cu I (NH 3 ) 2 ] + must migrate to the vicinity of another; enhanced in the presence of H 2 O 176–178 ) guarantees the formation of these dimeric Cu species, 90,166 thus improving the NH 3 -SCR-DeNO x activity. The 1Al–Cu species (located at isolated single Al sites, i.e.…”
Section: Reaction Mechanismsmentioning
confidence: 99%
“…179,180 The ratio of n (1Al–Cu)/ n (2Al–Cu) can be controlled through the catalyst's hydrothermal aging. 90 Krishna et al 181 suggested their perspective that spatial proximity of active Cu sites is required in the redox cycle of Cu 2+ /Cu + . Such proximity assists the oxidation of NH 3 -solvated Cu + ions to form dimeric Cu intermediates [Cu I (NH 3 ) 2 ] + –O 2 –[Cu I (NH 3 ) 2 ] + .…”
Section: Reaction Mechanismsmentioning
confidence: 99%
“…[24][25] Copper ions bound to cationic sites become mobile when they are solvated by water ligands and migrate from cage to cage, making the formation of copper dimers, necessary for re-oxidation in the selective catalytic reduction (SCR), facile. [26][27][28][29][30] In contrast, water is an obstacle in palladium ion exchanged zeolites used as passive NOx adsorbers (PNA) at low temperatures. [31][32][33][34][35][36][37] In zeolite-based PNAs (SSZ-13, ZSM-5, BEA) Pd ions efficiently trap NO in nitrosyl complexes, i.e., Pd 2+ -NO.…”
Section: Introductionmentioning
confidence: 99%